2006
DOI: 10.1089/jop.2006.22.79
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effects of Brimonidine and Dorzolamide on Ocular Blood Flow Velocity in Patients with Newly Diagnosed Primary Open-Angle Glaucoma

Abstract: The aim of this study was to evaluate the effects of brimonidine 0.2% and dorzolamide 2% on the ocular blood flow velocity in patients with newly diagnosed primary open-angle glaucoma (POAG). Forty-four (44) patients with newly diagnosed POAG were included in a prospective, comparative, randomized clinical study. Twenty-six (26) healthy volunteers, whose age and gender matched, were recruited to compare the baseline hemodynamic characteristics of the patients. After a complete eye examination, baseline blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Twenty-three prospective observational studies of 1286 eyes with POAG and 1052 controls were included in the meta-analysis. Eighteen of the studies concerned POAG eyes that received IOP-lowering drugs and had well controlled IOP [14], [21], [28]–[43]; five studies concerned newly diagnosed and untreated POAG [19], [44][47]. CDI was conducted in a sitting position in three studies [31], [40], [44] and in a supine position in the remaining 20 studies [14], [19], [21], [28]–[30], [32][39], [41]–[43], [45][47].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three prospective observational studies of 1286 eyes with POAG and 1052 controls were included in the meta-analysis. Eighteen of the studies concerned POAG eyes that received IOP-lowering drugs and had well controlled IOP [14], [21], [28]–[43]; five studies concerned newly diagnosed and untreated POAG [19], [44][47]. CDI was conducted in a sitting position in three studies [31], [40], [44] and in a supine position in the remaining 20 studies [14], [19], [21], [28]–[30], [32][39], [41]–[43], [45][47].…”
Section: Resultsmentioning
confidence: 99%
“…16 However, the effect of IOP-lowering medications on ocular blood flow remains poorly understood. Most studies have shown no change in retinal blood flow after treatment with timolol 17,18 or brimonidine 19,20 and a decrease in blood velocity of the ophthalmic artery after treatment with xalatan in POAG. 21 In particular, treatment with carbonic anhydrase inhibitors (CAIs) has been reported to increase ocular hemodynamics in POAG, 18,[22][23][24][25][26] to increase cerebral hemodynamics in young subjects, 27 and also to result in an enhanced autoregulation of retinal vessels after treatment with dorzolamide.…”
mentioning
confidence: 99%
“…21 In particular, treatment with carbonic anhydrase inhibitors (CAIs) has been reported to increase ocular hemodynamics in POAG, 18,[22][23][24][25][26] to increase cerebral hemodynamics in young subjects, 27 and also to result in an enhanced autoregulation of retinal vessels after treatment with dorzolamide. 28,29 A few studies have found no change 20,30,31 in retinal hemodynamics after CAI treatment. Most of the studies have assessed only the effect of CAIs in either patients receiving prior treatment or after an inadequate washout period.…”
mentioning
confidence: 99%
“…On the basis of these observations, it must be emphasized that modern antiglaucoma therapies should aim to affect not only intraocular pressure, but also other factors such as ocular blood flow. Although the effects of topical CAI drugs on ocular blood flow velocities were measured and the evidence obtained from these studies suggests that CAI agents increase the ocular blood flow velocities, the effect of these types of drugs was not investigated on primary open angle glaucoma patients with pseudoexfoliation [3–6,15]. The resistive index lowering effect of dorzolamide can be related to its vasodilator effect on ophthalmic and retinal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The major role of carbonic anhydrase inhibitors (CAIs) on intraocular pressure (IOP) is reducing aqueous humor secretion by inhibition of carbonic anhydrase in the ciliary processes. In addition to IOP lowering effect of this group drugs, dorzolamide and brinzolamide also increase the retrobulbar ocular blood flow by arterial vasodilation [3–6]. Several studies, using different methods, indicated that dorzolamide reduced retrobulbar ocular blood flow [7–9].…”
Section: Introductionmentioning
confidence: 99%